2014
DOI: 10.1080/15248372.2013.768245
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Explicit and Implicit Contrast in Verb Learning

Abstract: Contrast information could be useful for verb learning, but few studies have examined children’s ability to use this type of information. Contrast may be useful when children are told explicitly that different verbs apply, or when they hear two different verbs in a single context. Three studies examine children’s attention to different types of contrast as they learn new verbs. Study 1 shows that 3 ½-year-olds can use both implicit contrast (“I’m meeking it. I’m koobing it.”) and explicit contrast (“I’m meekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Contrast information has been shown to facilitate children's word learning and extension in a variety of tasks (e.g. Ankowski, Vlach & Sandhofer, 2013; Childers, Hirshkowitz & Benavides, 2014; Namy & Clepper, 2010; Waxman & Klibanoff, 2000). In prior cross-situational learning studies, implicit contrast could have encouraged children to form one-to-one mappings between words and objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast information has been shown to facilitate children's word learning and extension in a variety of tasks (e.g. Ankowski, Vlach & Sandhofer, 2013; Childers, Hirshkowitz & Benavides, 2014; Namy & Clepper, 2010; Waxman & Klibanoff, 2000). In prior cross-situational learning studies, implicit contrast could have encouraged children to form one-to-one mappings between words and objects.…”
Section: Introductionmentioning
confidence: 99%
“…First, labeling both referents provides implicit contrast information: if a child sees two objects and hears bosa and manu, this implies that one of these objects is a bosa while the other is not a bosa. Contrast information has been shown to facilitate children's word learning and extension in a variety of tasks (e.g., Ankowski, Vlach, & Sandhofer, 2013;Childers, Hirshkowitz, & Benavides, 2014;Namy & Clepper, 2010;Waxman & Klibanoff, 2000). In prior cross-situational learning studies, implicit contrast could have encouraged children to form one-to-one mappings between words and objects.…”
Section: Referential Ambiguitymentioning
confidence: 99%
“…Specifically, there are studies that show that variation across events can help children learn verbs (e.g., Childers, 2011; Childers, Heard, Ring, Pai, & Sallquist, 2012; Childers & Paik, 2009). For example, in one study, 2½-year-olds shown varied events performed as well as a set of children who received direct instruction on a new verb’s meaning (Childers, Hirshkowitz, & Benavides, 2014). Additionally, a study by Waxman, Lidz, Braun, and Levin (2009) shows that 2-year-olds who saw four comparison events and a contrast phase before test learned verbs, but it is unclear whether the comparison trials, the contrast trial, or both contributed to their performance at test.…”
Section: Do Children Use Variability Information Across Multiple Exammentioning
confidence: 99%
“…Multiple drafts are submitted for revision in stages. These thesis papers have been great starts to papers that can later be submitted for publication with student(s) as a co-author (Childers et al, 2012, 2014, 2016; Phillips et al, 2018;Phillips et al, 2019).…”
Section: Designing Research Procedures For Undergraduate Rasmentioning
confidence: 99%